Evaluation of arragement and use of green open space in Cimahi City’s Rusunawa - Enrico Nirwan Histanto; Yohanes Karyadi Kusliansjah (ARTEKS : Jurnal Teknik Arsitektur, 2018)
Cimahi City was originally one part of Bandung Regency, with rapid growth finally established as an administrative city on January 29, 1976, then became autonomous city on June 21, 2001. Cimahi currently become one of the growth areas of Bandung in the West. The current population is 561,386, with an average growth of 2.12% per year (source: population database of Cimahi City 2014). Green Open Space (RTH) in several cities in West Java has decreased both in terms of quality and quantity. This has the effect of reducing urban environmental quality and causing urban problems such as floods, especially in the rainy season, increasing air pollution, and decreasing urban happiness index due to the lack of open space available for social interaction. The similarity of the configuration of the arrangement of the site in this case the similarity of the typology of building mass composition, the number of occupants and the target of the residents of low income (MBR) of the two rusunawa Cimahi City, namely Cibeureum and Leuwigajah interesting to examine which is more effective the arrangement of green space and its utilization and the determinants what's playing. In the management, maintenance and utilization of the flats RTH is the main responsibility of apartment managers, in this case the Cimahi Municipal Government, but the involvement of all residents in maintaining and maintaining cleanliness, especially in disposing of waste in place and use the facilities provided responsibly.